An overview of breast cancer diagnostic techniques / Mohammad Mahdi Aeinehvand - Mohammad Mahdi , Aeinehvand (2012)
Breast cancer threatens many women, and early detection is a primary part of controlling and managing this disease. Mammography is widely used for the detection of breast cancer, but as this modality exposes women to ionizing radiation which can be a dangerous effect on their health, there are some doubts whether or not women under the age of 50 should be exposed to x-ray Mammography or not as a demand to detect breast cancer at early stages. Early detection of breast cancer plays a key role in rescuing lives which results in better quality of life. Many modalities used for detection of breast cancer still suffer some deficiencies such as the failure of mammography to detect 20%of the tumors, its uncomfortability to many of the patients in addition to considering it as a threatening source for the patients due to the increase of the possibility of cancer with the exposure repetition to the x-rays of the mammograms. Other modalities such as magnetic resonance imaging (MRI) and ultrasound are too expensive relatively. In this study a new technique using confocal microwave imaging (CMI) is studied. Breast tissue samples will be collected from department of surgery in UMMC. These samples will be subjected to study. Dielectric contrast between these samples will be determined based on their water content by utilizing the translucent characteristic of the breast. The tissue is to be determined whether it is cancerous or not using simple signal shifting, and summing and complex image composing algorithms is to be avoided. The permittivity values of normal and cancerous breast tissues also to be measured and compared. The digitized image of a cancerous breast tissue formed by hemispherical breast model using simple signal shifting is also to be studied.